Investigation of convective heat transfer coefficient and initial temperature of waxy crude oil on the formation of voids - Chala, Girma T.*; Shaharin, A. Sulaiman; Azuraien, Japper-Jaafar; Wan Ahmad Kamil, Wan Abdullah (UMP, 2016)
This paper presents the convective heat transfer coefficient of waxy crude oil while undergoing cooling and reports the influence of initial temperature on the intra-gel void formation. A flow loop rig was used to cool down waxy crude oil to the same end temperature while varying the initial temperature to observe the effects of initial temperature on the voids formed. The convective heat transfer coefficient and heat transfer rate of waxy crude oil subjected to cooling were calculated. It was observed that the heat transfer rate and the convective heat transfer coefficient of waxy crude oil below the wax appearance temperature were much lower than that of the Newtonian liquid crude oil owing to the wax crystal formation entrapping some liquid crude oil within it, below which the formation of voids is eminent. In addition, it was found that lower initial temperatures tend to form higher void volumes near pipe walls and in the entire pipe with a maximum change in void volume of 0.9% observed between the maximum and the minimum initial temperature tested. The insignificant influence of initial temperature on intra-gel void formation was also observed as the waxes are liquid above the wax appearance temperature.